2014
DOI: 10.2478/s11756-014-0481-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the canopy in the natural regeneration of Quercus robur in NW Spain

Abstract: The problem of natural regeneration of forests, in general, is essential especially under the climate change scenario. The canopy influence on the establishment and growth of oak seedlings supposes an approximation to the still lack of knowledge of oak forests heterogeneity. The management directly concerns the radiation that absorbs the canopy and, therefore, to the undergrowth radiation. The aim of the study was to research the existing relationships between the light percentage that crosses the canopy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…All of the these species have dense crowns that transmit less light. We think that light conditions were the key factor, as the light requirement of oak increases with increasing tree age and size (Lupke and Hauskeller-Bullerjahn, 1999;Vizoso-Arribe et al, 2014). Annighöfer et al, (2015) also showed that the occurrence of oak saplings was related to light conditions and that abundance increased with increasing light availability.…”
Section: Regeneration Of Oak Saplingsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the these species have dense crowns that transmit less light. We think that light conditions were the key factor, as the light requirement of oak increases with increasing tree age and size (Lupke and Hauskeller-Bullerjahn, 1999;Vizoso-Arribe et al, 2014). Annighöfer et al, (2015) also showed that the occurrence of oak saplings was related to light conditions and that abundance increased with increasing light availability.…”
Section: Regeneration Of Oak Saplingsmentioning
confidence: 99%
“…or common beech (Fagus sylvatica L.) has been detected in many aging Scots pine forests (Zerbe 2002;Dobrowolska 2006;Kint et al 2006;Gniot 2007;Goris et al 2007). However, spontaneous natural regeneration established under the Scots pine layer is not often used, even though it can play a great role in the restoration processes of forest stands and enhances their adaptability to changing environmental conditions (Diaci et al 2008;Vizoso-Arribe et al 2014). The success of spontaneous oak regeneration depends heavily on animal activity.…”
Section: Introductionmentioning
confidence: 99%
“…The undergrowth plays an important role in stands of natural regeneration processes [4]. New oak stands depend on their stand and underbrush density (which determines the lighting conditions) as well as on herbs and shrubs, canopy density and aggressiveness, e.g., the species' composition and sward formation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The success of oak natural regeneration depends on many factors, namely on a quantity of oak in the stand and its age, relative density of stocking, seed yield of acorns, a sufficient warmth, moisture, and finally light and development of the shrub and grass layers (Ikauniece et al, 2012;Vizoso-Arribe et al, 2014;Muhamed et al, 2015;Woziwoda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%